Estimating the generation of household e-waste in municipalities using primary data from surveys: A case study of Sao Jose dos Campos, Brazil - Abbondanza, M. N.M. [UNESP]; Souza, R. G. [UNESP] (Elsevier, 2019)
Estimating the generation of Waste from Electrical and Electronic Equipment (WEEE) in municipalities is relevant for the adequate planning of take-back systems. However, current WEEE estimation studies have focused primarily at the country level, and relied mostly on secondary data from literature, especially when adopting discrete average lifespans for each type of appliance. This paper aims at developing and applying a WEEE estimation method in a Brazilian city, by obtaining primary data that reflects the differences in WEEE generation among the various social and economic profiles in the city. A survey with a stratified sample was carried out to collect representative data from each city Zone. Results show that lifespan distributions are most desirable for WEEE estimation studies than discrete averages, and that the lifespan profiles in the city are considerably different than previous values adopted in other Brazilian studies. Results also show significant variations of lifespan profiles for different types of WEEE among the different Zones of the city, which reflect the social and economic differences.
Keywords: E-waste; E-waste generation; Waste from Electrical and Electronic Equipment (WEEE); WEEE generation